Answer:
The equation of the line is y = -1
Explanation:
In order to find the equation,y = mx + c, you have to find the gradient first using the formula :
![m = (y2 - y1)/(x2 - x2)](https://img.qammunity.org/2021/formulas/mathematics/college/l0kju436cyf4nxoay49vzskf4etr66w80u.png)
Let (x1,y1) = (-8,-1) & (x2,y2) = (-8,-1),
m = (-1)-(-1)/-8-(-8)
= 0
Now, we have found the gradient, next using the formula, y = mx + c to find the equation :
y = mx + c
Let m=0,
At (-8,-1)
-1 = 0(-8) + c
c = -1
y = -1